ESTIMATING AND ANALYZING THE TECHNICAL EFFICIENCY OF COMMERCIAL BANKS IN THE GAMBIA (Third Sector Social Economic Review, 2020)
The banking industry around ihe globe plays an important role by channeling funds from found providers to found users, which eventually contribute to the economic growth of many countries. Thus, the banking sector needs to operate efficiently to face changes in technology, regulations, and competition. This study estimates and analyzes the technical efficiency of commercial banks in the Gambia, employing the non-parametric Data Envelopment Analysis (DEA) method under Constant Return to Scale and Variable Return to Scale from 2009 to 2017. Also, the study uses the Tobit regression method to measure ihe determents of banks' efficiency in the Gambia during the same period, based on the intermediation approach. The DEA results show that commercial banks in the Gambia are not fully efficient in terms of technical efficiency, pure technical efficiency, and scale efficiency, implying that there was an effect of unnecessary extra costs on the banks' performance in The Gambia.
Keywords: Technical Efficiency; DEA; Tobit regression; Commercial Banking; The Gambia